Relationship between Neovascular Density in Swept Source-Optical Coherence Tomography Angiography and Signs of Activity in Exudative Age-Related Macular Degeneration - Martin Stattin; Julia Forster; Ahmed Daniel; Alexandra Graf; Katharina Krepler; Siamak Ansari-Shahrezaei (Journal of Ophthalmology)
Purpose. To assess the relationship between signs of activity in exudative neovascular age-related macular degeneration (nAMD) following anti-vascular endothelial growth factor (anti-VEGF) treatment and morphology of choroidal neovascularization (CNV) based on neovascular density as imaged using swept source-optical coherence tomography angiography (SS-OCTA) in a qualitative manner. Methods. A single-cohort retrospective data analysis from one tertiary eye care center. Seventy-seven eyes of 72 patients were included and their charts reviewed which had been started on intravitreal injections with anti-VEGF for nAMD at least one year prior to enrollment. Clinically active disease was evaluated by slit-lamp fundus examination and spectral domain-OCT B-scans. Morphological appearance in SS-OCTA was characterized based on 5 different criteria and subsequently divided into 3 groups: predominantly hyperdense, minimally hyperdense, and hypodense lesions. Results. Fifty-eight eyes (75%) were considered clinically active and 19 eyes (25%) clinically inactive. CNV was depicted in 71 eyes (92%) by SS-OCTA and separated accordingly into predominantly hyperdense (32%), minimally hyperdense (34%), and hypodense lesions (34%). A borderline significant difference in the probability of neovascular activity for predominantly hyperdense lesions compared to hypodense lesions was detected (p=0.05). Conclusions. Hyperdense choroidal neovascularization based on qualitative assessment of flow density showed a significant relation to active disease. Inactivity could not be matched adequately. This study demonstrated the potential usefulness of SS-OCTA for guidance of treatment in age-related macular degeneration.